New data on the occurrence and status of some sparid species (Actinopterygii: Sparidae) in the coastal Bulgarian Black Sea waters - Feriha M. Tserkova; Vesselina V. Mihneva; Elitsa P. Petrova-Pavlova; Tihomir Stefanov; Krasimir Georgiev; Stanimir Valchev; Zahari Marinov; Mak Goranov; Radinela Stefanova; Lidia Nedkova (Historia naturalis bulgarica)
Fish species diversity in the Black Sea is affected by a phenomenon called mediterranisation. This is related to the advance of thermophilic fish from the Mediterranean Sea into the Black Sea. Although sparid species have been noted in the Black Sea, detailed information regarding their occurrence and recent status remains limited. In 2022-2023, we collected data on three sparid species in Bulgarian coastal waters. These species included Spicara smaris (Linnaeus 1758), Lithognathus mormyrus (Linnaeus 1758), and Diplodus puntazzo (Walbaum 1792). This study provides new localities and quantitative data for these sparid species in the coastal zone of Bulgarian Black Sea.